Economic Analysis of Giant Shrimp Cultivation in the Ngusa Taka Group in Sengkong Village, Sesayap Hilir District, Tana Tidung Regency - Fitriyana Fitriyana; Helminuddin Helminuddin; Yudha Yudha (Budapest International Research and Critics University, 2022)
This research is about economic analysis of giant shrimp cultivation in the Ngusa Taka Group in Sengkong Village, Sesayap Hilir District, Tana Tidung Regency. Carrying out this research for 3 months starting on August 1, 2021 until October 31, 2021 with the object of research being giant shrimp cultivation which is the “Ngusa Taka Group” in Sengkong Village, Sesayap Hilir District, Tana Tidung Regency. The number of cultivators of giant shrimp in the Ngusa Taka Group is 20. Sampling in this study used the census method. Then obtained the number of respondents who will be used in this study as many as 20 cultivators of giant shrimp. The data obtained from the research results will be processed and analyzed and then presented in the form of tables and schematics as well as descriptive descriptions. Giant shrimp cultivation in the Ngusa Taka Group in Sengkong Village, Sesayap Hilir District, Tana Tidung Regency based on indicators of revenue cost ratio, break even point, payback period, and return on investment, obtained the results of the analysis that this business is feasible to continue.